RESPON MALAYSIA TERHADAP KEBIJAKAN SINKING-SHIP INDONESIA - Wulan Nurul Hakim (Andalas Institute of International Studies, 2019)
This research describes the Malaysian policy as a response to the Indonesian sinking-ship policy executed in 2014. This research uses qualitative research approach with descriptive analysis method. This research applied the concept of Foreign Policy Change by Tomas Niklasson with three indicators, the degree of foreign policy change (adjustment, reform, restructuring), time-frame for change (rapidly or gradually) and the scope of foreign policy changes (regulatory, security, trade and economic stability, national identity and autonomy). In this research categorizes that responses of sinking-ship policy at the level of adjustment (minor change) due to a little change and categorizes at the rapidly because of rapid responses and less than five years. In the scope of policy change indicators, this research found that the changes in two policies, security and economy.